Reliability of radioisotope-guided sentinel lymph node biopsy in penile cancer: verification in consideration of the European guidelines. Issue 1 (December 2015) - Schubert, Tim; Uphoff, Jens; Henke, Rolf-Peter; Wawroschek, Friedhelm; Winter, Alexander
Abstract Background Lymph node (LN) staging in penile cancer has strong prognostic implications. This contrasts with the high morbidity of extended inguinal LN dissection (LND) or over-treatment of many patients. Therefore, inguinal dynamic sentinel node biopsy (DSNB) or modified LND is recommended by the European Association of Urology (EAU) guidelines to evaluate the nodal status of patients with clinically node-negative penile cancer. This study analyzed the reliability and morbidity of radioguided DSNB in penile cancer under consideration of the current EAU recommendations in an experienced center with long-term follow-up. Methods Thirty-four patients who received primary surgery and had radioguided inguinal DSNB for penile cancer (≥T1G2) were included (July 2004 to July 2013). Preoperative sentinel LN (SLN) mapping was performed using lymphoscintigraphy after peritumoral injection of99m Technetium nanocolloid on the day of surgery. During surgery, SLNs were detected using a gamma probe. According to the EAU guidelines, a secondary ipsilateral radical inguinal LND was performed in patients who had positive SLNs. The false-negative and complication rates of DSNB were assessed. Results A total of 32 patients were analyzed. Two patients were lost to follow-up. A total of 166 SLNs (median, 5; range, 1–15) were removed and 216 LNs (SLNs + non-SLNs; median, 6; range, 2–19) were dissected. LN metastases were found in five of the 32 (15.6 %) patients and nine of the 166 (5.4 %) SLNs were found to contain metastases. None of the remaining 50 non-SLNs contained metastases. In only one of the five SLN-positive patients, a singular further metastasis was detected by secondary radical inguinal LND. During follow-up (median, 30.5; range, 5–95 months) no inguinal nodal recurrence was detected. DSNB-related complications occurred in 11.1 % of explored groins. Discussion and Conclusions Radioguided DSNB is a suitable procedure for LN staging in penile cancer considering the EAU recommendations and with the required experience. Under these circumstances, patients can be spared from higher morbidity without compromising the detection of LN metastases or therapeutic implications. Improvement of the methodology used to perform DSNB should be developed further to decrease the risk of missing LN metastases and to simplify the procedure.